1982
DOI: 10.1007/bf02374729
|View full text |Cite
|
Sign up to set email alerts
|

Root development of vegetable crops

Abstract: SummaryMeasurements were made at intervals during the growth of seven different vegetable crops grown on the same soil to find how far root development and crop growth could be described by simply derived equations and to find how far the parameter values varied from crop to crop.For each crop K1 In W + W, (where W is total plant dry weight, t ha-t and K 1 is equal to 1 t ha -1) was linearly related to time from emergence, as in past experiments.The derived equationwhere L is total root length per unit area, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(66 citation statements)
references
References 20 publications
9
56
1
Order By: Relevance
“…Generally, P acquisition by crop plants is accomplished by extending roots into soil. Crop plants of Alliaceae, such as Welsh onion, onion, Chinese chive, garlic, and leek, have a less welldeveloped root system than most other species (Greenwood et al 1982). Studies have shown that the inoculation of AM fungi improved P uptake and growth of Allium cepa (Mosse and Hayman 1971;Smith et al 1986), Allium fistulosum (Tawaraya et al 1999(Tawaraya et al , 2001, and Allium porrum (Hepper et al 1988;Stribley et al 1980) under the pot culture condition.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, P acquisition by crop plants is accomplished by extending roots into soil. Crop plants of Alliaceae, such as Welsh onion, onion, Chinese chive, garlic, and leek, have a less welldeveloped root system than most other species (Greenwood et al 1982). Studies have shown that the inoculation of AM fungi improved P uptake and growth of Allium cepa (Mosse and Hayman 1971;Smith et al 1986), Allium fistulosum (Tawaraya et al 1999(Tawaraya et al , 2001, and Allium porrum (Hepper et al 1988;Stribley et al 1980) under the pot culture condition.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, choosing crops with deep root systems is important for the possibility to utilise N retained from previous crops. Large differences in t he ability to take up N from deeper soil layers are found among vegetable crops (Burns, 1980;Greenwood et al, 1982;Thorup-Kristensen and Sørensen, 1999;Thorup-Kristensen, 2001). …”
Section: Resultsmentioning
confidence: 99%
“…Researchers use a variety of methods (cores, bags, excavation) to collect and study plant roots (Greenwood et al 1982;Steen 1985;Reid et al 1993). Roots were assessed from traces on acetate sheets, by various line intercept methods, and via direct measurements.…”
Section: Discussionmentioning
confidence: 99%
“…These measurements are then used to estimate turnover, biomass, root length, distribution or density, and nutrition. Root distribution studies have been conducted on a variety of annual vegetables (Greenwood et al 1982). They used soil-coring techniques, water extraction, alcohol preservative, and line intersect method to determine root length.…”
Section: Discussionmentioning
confidence: 99%